Cosmologies tangibles - Granö, Veli (CV Photo)

(untitled) (Les Productions Ciel variable, 2002)
Summary Today's collector is of a new kind: a historian, a restorer of meaning. This figure, the expert collector, shows us where our past is hidden and how we can rediscover it. Such collectors give meaning and historical perspective to everyday objects and convey this meaning to the millions of consumers who use the same objects. They are able to give a new value and content to objects that have been pronounced vain and condemned to destruction. They are champions of microhistory, history that is the size of the human experience of the everyday.